2011
DOI: 10.1007/s00520-011-1349-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer therapies in specialized palliative care—a multicenter survey

Abstract: IntroductionAnticancer therapies gain increasing attention and discussion in specialized palliative care institutions. Frequency, indication, attitude of team members, and modes of these therapies implemented in specialized palliative care settings are still under investigation.MethodsDescriptive analysis of the nationwide Hospice and Palliative Care Evaluation 2007 that collected data from palliative medicine, hospice care, and oncology institutions concerning the use of anticancer therapies.ResultsThree thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…One full-text paper and seven abstracts assessed the use of thromboprophylaxis in palliative care units, with all demonstrating low rates of initiation or continuation of thromboprophylaxis. 39,44,45,47–50 Overall, thromboprophylaxis was initiated in 4%–53% of admitted patients. 39,45…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One full-text paper and seven abstracts assessed the use of thromboprophylaxis in palliative care units, with all demonstrating low rates of initiation or continuation of thromboprophylaxis. 39,44,45,47–50 Overall, thromboprophylaxis was initiated in 4%–53% of admitted patients. 39,45…”
Section: Resultsmentioning
confidence: 99%
“…44 Brabin et al 45 also found low rates of thromboprophylaxis initiation (3 of 75 patients) with documentation of decision-making recorded only in approximately one-third. Alt-Epping et al’s 48 survey of nine palliative care units and one residential hospice ( N = 233) in Germany reported thromboprophylaxis use in 68 patients (29%): 4 developed venous thromboembolism and 1 bleeding. Ciuhu et al 46 retrospectively reviewed the use of anticoagulants on a palliative care unit over a 6-month period ( N = 2642); 13.6% of admissions were considered for antithrombotic therapy, which was thromboprophylaxis in 81%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Daten aus HOPE wurden bereits mehrfach für wissenschaftliche Studien herangezogen [2,21,24,29,33]. Die vorliegende Untersuchung beruht auf HOPE-Daten aus spezialisierten stationären Hospiz-und Palliativeinrichtungen aus den Jahren 2006 -2008.…”
Section: Methodenunclassified